The Academic and the Advocate: A foot in both camps - Liddy, Susan (Irish Journal of Arts Management and Cultural Policy, 2023)
A personal reflection on the challenges and rewards of working as an advocate and an academic, Dr Susan Liddy looks back over her career to date and how she has endeavoured to advance the position of women, including older women, in the Irish screen industry. She discusses the resistance to change she met in the early days of her research and the failure of agencies to take an active approach to advancing women’s careers. She outlines the impact her findings have had in this area through media engagement and her realisation that she needed to publish in public-facing outlets and to speak out at public events alongside maintaining a traditional academic profile (with articles in referred journals, as author of industry reports and editor of international collections). She notes the importance of international movements to advocate for gender balance and EDI, and the impact of the #WakingTheFeminists movement locally. Finally, she acknowledges the influence she has been able to wield through her increasing engagement with WFT (Women in Film and Television Ireland) and the importance of knowledge-sharing as a public intellectual and advocate.